UNDERSTANDING STOCK RETURN DRIVERS: THE INTERPLAY BETWEEN NET PROFIT, OPERATING CASH FLOW, AND DIVIDEND POLICY IN IDX QUALITY 30 COMPANIES - Deafatunnizwa Ulfida; Nor Rahma Rizka; Fitra Izzadieny; Try Edi Suwarno (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
This study examines the impact of stock price, net profit and operating cash flow on stock return, with the dividend serving as a moderating variable. The research focuses on companies listed on IDX Quality 30 companies over the period 2021 to 2024. The main problem addressed is the lack of comprehensive empirical evidence on how core financial performance indicators influence stock valuation within highly selective and fundamentally strong firms such as those in the IDX Quality 30 Index. Although these companies are considered financially robust and attractive to investors, there remains uncertainty about the relative importance of profitability, liquidity, and dividend policy in driving their market valuation. Recognizing the importance of financial performance indicators in stock valuation, this study seeks to determine whether stock price, net profit, netoperating cash flows significantly influence stock return, and whether dividend policy enhances this relationship. The analysis will employ multiple regression techniques to examine both direct and moderating effects. By incorporating operating cash flow alongside net profit, the study attempts to provide a more comprehensive understanding of the drivers of stock returns. While data collection and analysis are currently in progress, the findings are expected to contribute valuable insights to both investors and corporate decision-makers regarding financial strategy and market perception. Future stages of the research will include empirical testing, interpretation of results, and implications for investment practices and corporate policy.